Comparison of Hair Cortisol Levels and Perceived Stress in Mothers Who Deliver at Preterm and Term. Issue 3 (May 2018) - Duffy, Allyson R.; Schminkey, Donna L.; Groer, Maureen W.; Shelton, Melissa; Dutra, Samia
Objective: To evaluate relationships between hair cortisol levels and perceived stress in mothers who deliver preterm and term. We hypothesized that the rate of change in cortisol levels would be greater in the preterm delivery group. Methods: This preliminary study compared hair cortisol levels and Perceived Stress Scale (PSS) scores in predominately Caucasian mothers who delivered preterm ( n = 22) and term ( n = 30). We collected PSS and hair samples of ≥10 cm in length from mothers after delivery. Hair was segmented into three sections, and cortisol was measured using enzyme-linked immunosorbent assay. Results: The mean gestational age was 31.45 ( SD = 4.2) weeks for preterm deliveries and 39.45 ( SD = 1.1) for term. Cortisol differed significantly in the third trimester between mothers delivering term and preterm ( t = 2.16, df = 48, p = .04) and trended toward significance in the second trimester ( t = 1.88, df = 48, p = .06). PSS differed significantly between the two groups ( t = −2.96, df = 50, p = .05). Our data did not provide support for our hypothesis. Conclusion: There appeared to be a blunted, flattened pattern of change in cortisol levels across gestation in the women who delivered preterm, suggesting diminished hypothalamic–pituitary–adrenal axis responsiveness in mechanisms that promote preterm labor. Future studies are needed to further evaluate best strategies for measuring the mechanisms of allostatic load during pregnancy along with the psychoneuroendocrine and immune triggers and placental responses that lead to premature birth.